Interactions between Equity REITs and S&P 500 Returns - Rahman, Matiur (International Journal of Economics and Financial Issues, 2024)
This paper seeks to reinvestigate the contemporaneous interactions using daily closing prices of US eREIT and S&P 500 indices to calculate their respective rates of return. Daily data are used from October 31, 2008 through October 31, 2023 with 3,856 observations. Data are obtained from (www.wsj.com and (https://finance.yahoo.com/). The time series data distributions of both variables are near-normal in term of their respective mean-to-median ratio with very low standard deviations. The Ordinary Least Squares (OLS) is applied to estimate regressions (1) and (2) for reliable and unbiased results, as it meets the statistical criteria for suitability. The regression results show evidence of weak interactions between them with bidirectional causal flows.